Dialysis Toolkit for Severe Thrombocytopenia in Patients with Acute Kidney Injury - Sourabh Sharma; Intissar Haddiya; Dina A Abdellatif; Sanjay Kalra (Journal of the Pakistan Medical Association, 2026)
Acute kidney injury (AKI) in the setting of severe thrombocytopenia represents a formidable challenge in nephrology, where both the underlying disease and therapeutic interventions carry a high risk of bleeding. Conditions such as lupus nephritis, thrombotic thrombocytopaenic purpura (TTP), haemolytic uraemic syndrome (HUS), haematological malignancies, chemotherapy-induced marrow suppression, and severe viral infections including dengue or sepsis-related disseminated intravascular coagulation often present with simultaneous kidney dysfunction and profound thrombocytopenia. In such renothrombocytopenic syndromes, initiation of kidney replacement therapy (KRT) is often lifesaving but complicated by the heightened risk of haemorrhage because of various factors including anticoagulation use, vascular access placement, and fragile haemostasis. This article reviews the unique challenges of dialysis in patients with thrombocytopenia and proposes a structured “Dialysis Toolkit” for clinicians. Keywords: Acute kidney injury, bleeding diathesis, dialysis, haemodialysis, rapidly progressive renal failure, renal replacement therapy, thrombocytopenia,